Development of the system of energy and resource saving during the operation of the gas pumping unit - Kologrivov, Mykhailo; Buzovskyi, Vitalii (Technology audit and production reserves, 2021)
The object of research is the fuel gas system of a gas turbine engine. The study of the use of secondary energy resources of the gas-pumping unit at the compressor station of the main pipeline has been carried out. The work of a gas turbine engine, including the work of the fuel gas system, is considered. The main drawback of the fuel gas system is revealed – ineffective use of excess gas pressure. An informational analysis of the options that eliminate the identified drawback is carried out. It is shown that in order to eliminate the disadvantage, it is advisable to use a turbo-expander at the compressor station to utilize the excess pressure of the fuel gas. It is also shown that the operation of a fuel gas turboexpander to drive an additional air compressor as part of a gas turbine engine is impractical. An expander-generator set with the generation of additional electricity at the compressor station is recommended for use. Modeling the operation of the utilization system made it possible to recommend constructive proposals for its improvement. A schematic diagram of a system for the complex utilization of excess pressure of fuel gas and heat of combustion products from the operation of a gas turbine engine is proposed. The system of complex utilization includes parts-generator unit, heat exchanger for cooling process gas and heat exchanger for firing gas. Regenerative heating of fuel gas up to 250 °С reduces energy consumption for heating it up to the ignition temperature. A model of a robot installation of the type GPU 16/56-1.44 (Ukraine) is carried out. It is determined that when a component engine of the J-59 (Ukraine) type with a shaft power of 16 MW operates, it is possible to additionally receive 102 kW of electricity and save 64 m3/h of fuel gas. It is revealed that the subcooling of the process gas does not play a significant role in reducing energy consumption during its transportation. It is recommended to use the process gas to heat the cold fuel gas stream downstream of the turboexpander to positive temperatures. The integrated utilization system is not a simple connection of an expander-generator set and two heat exchangers along the flow of the fuel gas. As a result of its operation, a significant reduction in the consumption of fuel gas and electricity is achieved. The disadvantages that hinder the implementation of a comprehensive disposal system are identified. This is the use of equipment for generating electricity at a compressor station. It is uncharacteristic for the operation of the station and requires additional qualifications in service. It is also required that the characteristics of industrial expander-generator sets correspond to the fuel gas consumption of a gas turbine engine.